2003
DOI: 10.1093/nar/gkg820
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the design horizon of antisense oligonucleotides with alpha-L-LNA

Abstract: Oligonucleotides containing Locked Nucleic Acids (LNA) to various extents and at various positions were evaluated for antisense activity, RNase H recruitment, nuclease stability and thermal affinity. In this work, two different diastereoisomers of LNA were studied: the beta-D-LNA and the alpha-L-LNA (abbreviated as beta-D-LNA and alpha-L-LNA). Our findings show that the best antisense activity with 16mer gapmers containing beta-D-LNA (oligonucleotides containing consecutive segments of LNA and DNA with a centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 15 publications
2
59
0
Order By: Relevance
“…Interestingly, the MOE 16mer 2a had greatly reduced potency, whereas the potency of the 16mer LNA 2b was improved relative to the 18mer LNA ASO 1b. These results are consistent with a previous study of LNA ASOs (37), in which the high affinity of LNA facilitated good target reduction with 16mer LNA ASO designs.…”
Section: Resultssupporting
confidence: 93%
“…Interestingly, the MOE 16mer 2a had greatly reduced potency, whereas the potency of the 16mer LNA 2b was improved relative to the 18mer LNA ASO 1b. These results are consistent with a previous study of LNA ASOs (37), in which the high affinity of LNA facilitated good target reduction with 16mer LNA ASO designs.…”
Section: Resultssupporting
confidence: 93%
“…The DNAzymes and LNAzymes were synthesized by Santaris Pharma A/S (Hørsholm, Denmark), as described previously (Frieden et al, 2003). In all ODNs, 5-methyl-C was used.…”
Section: Lna Odn Synthesismentioning
confidence: 99%
“…Also Elmén et al (2004) demonstrated that LNA/DNA mixmers activate RNase H when the mixmer has a DNA stretch of 6 nt. In accordance, Frieden et al (2003a) concluded that a DNA gap size between 7 and 10 nt is optimal for LNA/DNA/LNA antisense gapmers. The overall conclusion is that antisense LNA oligonucleotides can be designed to elicit RNase H activity while still containing LNA monomers for improved binding and target accessibility (Jepsen and Wengel 2004).…”
Section: Susceptibility Of Lna To Nucleasesmentioning
confidence: 81%